The Sources of Macroeconomic Fluctuations in Developing Countries : Brazil and Korea - Roldos, Jorge (IMF Working Papers; Working Paper ;, 1996)
This paper studies the sources of macroeconomic fluctuations in developing countries using a structural VAR approach. Identification of the sources is achieved using long-run restrictions derived from a theoretical model of a small open economy encompassing a large number of macroeconomic paradigms; the short-run dynamics are unrestricted. This framework is applied to Brazil and Korea. The results confirm that supply shocks are the main source of GDP fluctuations, even in the short run. Aggregate demand shocks are shown to be important in the short run in Brazil, but not in Korea. External shocks explain a small fraction of the variance of output, whereas the real exchange rate is driven mainly by fiscal shocks. Nominal shocks appear to have little impact on output and the real exchange rate.